واقع تحقيق الأسرة السعودية لمفهوم الاستهلاك المستدام: دراسة ميدانية مطبقة على عينة من الأسرة السعودية - الزهراني، ناصر عوض صالح (جامعة أم القرى, 2017)
تنتمي هذه الدراسة للدراسات الوصفية، التي هدفت بشكل رئيس إلى الكشف عن واقع تحقيق الأسرة السعودية لمفهوم الاستهلاك المستدام، وذلك من خلال محاولة رصد عادات المجتمع السعودي الاستهلاكية في حياتهم اليومية بشكل عام، وكذلك فيما يتعلق بممارساتهم في استهلاك بعض الجوانب المرتبطة بالاستهلاك المستدام مثلاً: الطاقة الكهربائية، والبترولية، واستهلاك الأغذية، والملبوسات، والمياه، والكشف عن مدى قرب أو بعد هذه الممارسات عن مفهوم الاستهلاك المستدام كما هدفت من ناحية أخرى للكشف عن مدى وجود فروق ذات دلالة إحصائية بين النمط السائد للاستهلاك وبين بعض الخصائص الديموغرافية للعينة، ولتحقيق الأهداف السابقة استخدمت الدراسة طريقة المسح الاجتماعي بالعينة وجمعت بياناتها عن طريق الاستبانة من عينة الدراسة التي بلغت (1345) أسرة سعودية تم اختيارهم بواسطة العينة العشوائية البسيطة، وكشفت الدراسة عن مجموعة من النتائج من أبرزها وفيما يتعلق بالاستهلاك عموماً وجد أن الصورة العامة تشير إلى انخفاض الوعي الاستهلاكي عند الأسر السعودية إذ إن الغالبية العظمى منهم ينجذبون ببساطة نحو شراء أشياء لم يكونوا مخططين لشرائها متأثرين بالإعلانات والتخفيضات التي تقدمها المتاجر، وعلى الرغم من ارتفاع مستوى دخل الأسر غير أن هذا النمط للنزعة الاستهلاكية السلبية أجبر معظمهم على الاستدانة واستخدام بطاقات الائتمان لتأمين بعض المتطلبات، التي وجد أن أكثر الجوانب التي تنفق عليها الأسر تتمثل في: الأكل والشرب ثم الاتصالات. وفيما يتعلق بالاستهلاك المستدام وجد أيضا أن هناك مؤشرات تدل على تدني الاهتمام بهذا الجانب ومن ذلك استخدام أجهزة التكييف والسيارات بشكل لا يعكس الاهتمام بالجوانب البيئية إذ اهتمت الأسر بجوانب الجودة والعلامة التجارية عند التفكير في اقتناء جهاز أو سيارة فيما أهملت الاهتمام بالبعد البيئي والذي سيؤثر بشكل سلبي على البيئة وذلك من خلال الانبعاثات والتلوث الذي تخلفه هذه الأجهزة، كما وجد أن استخدام الملابس والطاقة الكهربائية والبترولية والمياه كذلك يبتعد كثيرا عن مفهوم الاستهلاك المستدام إذ وجد أن هناك هدر كبير في هذه الجوانب يعكس عدم وعي الأسر السعودية بخطر الاستهلاك بهذه الصورة التي لا تراعي استدامة الموارد القابلة للنفاذ.
This study belongs to descriptive studies which mainly aimed at exploring the reality of achieving the concept of sustainable consumption by Saudi families through an attempt to monitor the Saudi society consumptive habits in their daily lives in general, and with regard to their practices in the consumption of some aspects associated with sustainable consumption, such as electric power, petroleum, and consumption of food, clothing, water, and reveal to what extent these practices are near to or far from the concept of sustainable consumption, It also aimed, from other hand at detecting the presence of significant differences between the prevailing pattern of consumption and some of the demographic characteristics of the sample . To achieve the former objectives, the study used the social survey method by sampling and gathered data through the questionnaire from the study sample, which amounted to (1345) Saudi families were selected by simple random sample. The study revealed a set of results, notably With regard to overall consumption it has been found that the general image refers to a decline consumptive awareness among Saudi families as the great majority of them buy things without any need to them , and they have been affected by advertisement and discounts offered by the vast stores. In spite of the high level of household incomes, this style to negative consumerism forced most of them to borrow and use credit cards to secure some of the requirements .It has been found that more aspects spent on families represented in eating & drinking, and communications. With regard to sustainable consumption also it found that there are indicators of poor attention to this aspect representing in the use of air conditioners and cars by a manner that reflects the non - attention to the environmental aspects. Hence, families interested in aspects of quality and brand when they think of the acquisition a device or a car with neglected attention to the environmental dimension which will impact negatively on the environment through emissions and pollution that caused by these devices, also found that the use of clothes and electrical petroleum, energy and water as well as stray far from the concept of sustainable consumption it found that there is a big waste of these aspects reflecting the lack of awareness at Saudi household belongs consumption in this picture that does not take into account the sustainability of the Focused on families aspects of quality and brand when you think of the acquisition device or a car with neglected attention to the environmental dimension which will impact negatively on the environment through emissions and pollution that failure of these devices, also found that the use of clothes and electrical petroleum, energy and water as well as stray far from the concept of sustainable consumption it found that there is a big waste of these aspects reflects the lack of awareness of the danger of the Saudi household consumption in this picture that does not take into account the sustainability of the Focused on families aspects of quality and brand when you think of the acquisition device or a car with neglected attention to the environmental dimension which will impact negatively on the environment through emissions and pollution that failure of these devices, also found that the use of clothes and electrical petroleum, energy and water as well as stray far from the concept of sustainable consumption it found that there is a big waste of these aspects reflects the lack of awareness of the danger of the Saudi household consumption in this picture that does not take into account the sustainability of resources which are about to finish.
Keywords: السعودية -- الاستهلاك المستدام -- السلوك الاستهلاكي -- التنمية المستدامة